INSTITUTIONAL SUPPORT, GREEN INNOVATION, AND FINTECH ADOPTION: SHAPING THE FUTURE OF SUSTAINABLE BANKING IN PAKISTAN - Mubeen , Yasir; Majeed, Dr. Muhammad Kashif; Sabir, Dr. Saba; Maqsood , Maria (International Research Journal of Social Sciences and Humanities, 2025)
The current paper investigates the relationship between the use of FinTech, Green Innovation (GI), and Banking Sustainable Performance (BSP) and their role in the banking industry of Punjab, Paksitan. The main aim is to examine how FinTech adoption affects sustainability in business practices by banks and to explain the mediation effect of Green Innovation and moderating influence of Perceived Institutional Support (PIS). Systematic questionnaire was used to Central 384 employees in the lead privatized banks in Punjab and the hypothesized relationships in the constructs were tested using Partial Least Squares Structural Equation Modeling (PLS-SEM). The empirical results have shown that the effect of FinTech adoption on BSP is either positive or negative, and GI is the mediating variable. In addition, PIS moderate the association between the FinTech adoption and GI, thus highlighting the importance of institutional facilitation of successful digital transformation in the banking industry. These findings indicate that FinTech and sustainability programs need to be combined to improve the overall performance of the bank. This research is relevant to the growing literature on sustainable banking as it presents empirical data of a developing economy; therefore, it has some important implications to policy-makers and financial institutions seeking to use FinTech to attain sustainable development.